Influence of heat treatment in sintering process on characteristics of Al2o3-Zro2ceramics systems - A. Rittidech (2018)
Al2O3-ZrO2ceramics containing 5-50 mol% ZrO2were prepared by solid state reaction method. The bulk density, average grain size and microhardness of Al2O3-ZrO2ceramics system as function of ZrO2content were investigated. The dense Al2O3-ZrO2Ceramics were successfully by means of carefully control processing parameters that include sintering temperature and heating/cooling rates. These ceramics with higher ZrO2content was obtained high bulk densities and small grain sizes. However, the high hardness values were exhibited from Al2O3-ZrO2ceramics with dopants ZrO2between 1-10mol% and its tend to decrease with concentration of ZrO2. It can be found that the fast heating/ cooling rates are controlled grain growth and obtained high hardness in materials. The results gave good correlation between stoichiometry characteristics, heating/cooling rates in sintering and microstructure of fabricated dense and mechanical properties. © 2009 Science Publications.